Production technology and carbon emission: Long-run relation with short-run dynamics - Soumyananda Dinda (Journal of Applied Economics, 2018)
Using a vector error correction model, this paper investigates the long-run relation with short-run dynamics among CO2 emission, technological progress and economic growth. It observes a specific kind of causality running from technological progress to reduction of CO2 emission in the United States during 1963-2010, while past income generation is the cause of rising carbon emission. Policy makers should emphasise R&D for updated production technology, while raising income helps to reduce CO2 emission. Technological progress is the central force that causes income growth as well as emissions' reduction. Continuous change and adaption of new and updated technology is the main driving force towards sustainable development.
Keywords: 330; CO2 emission; economic growth; patent; technological progress